Kasumba Turate As a Raw Material For Functional Herbal Drink - Nurfaillah, Nurfaillah; Yanto, Subari; Fadilah, Ratnawaty (Journal of Agroscience Indonesia, 2024)
Kasumba turate  is one of the functional herbal  plants because it contains polyphenols and  high  antioxidant  activity. Dried  kasumba  turate  flowers from farmers  have  varying concentrations  in each  plastic  packaging  so that  it can  affect the content  of the steeped kasumba turate.  This study aims to determine  the effect of differences in concentration  of kasumba turate  on the quality of functional herbal  drinks. The type of research  used was a completely randomized design with a quantitative  method consisting of one factor,  namely the concentration  of dried kasumba turate flowers. This study consisted of 3 treatments and 1 as control with 3 repetitions, namely: control (0.2 g), treatment A (0.6 g), treatment B (0.8 g), and treatment C (1 g). Each treatment was analyzed for moisture content, ash content, antioxidant  activity (IC50  ), polyphenol content, total  plate  number, and organoleptic  tests related  to  color,  aroma  and  taste.  The  results  showed  that  different  concentrations   of kasumba turate  had a significant effect on the quality of functional herbal  drinks based on water content, ash content, IC50 , polyphenol content, and taste organoleptic  tests. 50The best treatment  in this study was treatment  C with a concentration  of 1 gram of kasumba turate because it had an IC of 102.73 ppm in the medium category.